Aktivitas Ekonomi Masyarakat Nelayan di Desa Lamuru, Kecamatan Tellu Siattinge, Kabupaten Bone - Risa, Nurul Eka Wijayanti; Mapparimeng, Mapparimeng (Journal of Fisheries and Marine Applied Science, 2024)
. Economic activities carried out by fishing communities give color to the typical economic activities of coastal communities. These conditions arise from the interactions carried out by the community with their environment, thus forming daily economic activities. The method in this research uses qualitative descriptive analysis which aims to describe problems related to the focus of the research scope. The data obtained will be analyzed using the triangulation method by obtaining information through observation, surveys and structured interviews with several respondents. Lamuru Village is one of the villages located in the coastal area and directly borders Bone Bay. The location of the village in a coastal area means that the people in this area generally work as fishermen and some of the residents work as cultivators and other professions. The fishing work carried out by the community uses traditional, semi-modern and modern tools. Some of the people carry out fish farming, trade and some also have side jobs as farmers. From the activities they carry out, they get enough results to fulfill their family life.